Enhanced antioxidant activity of selenium-enriched brown rice protein against oxidative stress in mammalian erythrocytes under various cooking conditions - Muhammad Tayyab Rashid; Kunlun Liu; Mengru Ning; Kalim Ullah; Asif Wali; Mushtaq Ahmed Jatoi; Nazish Muzaffar (Journal of Agriculture and Food Research)
This study investigated the effects of Selenium-enriched brown rice protein on oxidative stress in the mammalian erythrocytes. Selenium-enriched brown rice protein and native rice protein (control) were treated with mice erythrocytes at various cooking processes. The research explored the antioxidant activity of enzymes, including superoxide dismutase (SOD), catalase CAT), and lipid peroxidase (LPO) as well as markers of oxidative damage such as malondialdehyde (MDA). Furthermore, the investigation analyzed the expression of proteins, including nuclear factor erythroid 2-related factor 2 (Nrf2), a principal regulator of the antioxidant response, and Band3, a membrane protein crucial for erythrocyte function. The study also examined the influence of different types of cooking on the effectiveness of selenium-enriched brown rice protein and native rice protein (control). Cooking increased the protection against oxidative damage of red blood cells; high-pressure cooking demonstrated the highest efficacy, followed by microwave cooking and low-pressure cooking. In addition, the results indicated that this protection mechanism might be related to the regulation of antioxidant enzyme activities and gene expressions induced by Peroxiredoxins (PRP) protein, Band3, and Nrf2 genes, leading to decreased lipid peroxidation and oxidative product generation. This contributed to the preservation of RBC integrity and decreased the rate at which it was Hemolysis. Our findings suggest that the protective mechanism of PRP against oxidative damage in RBCs is associated with the regulation of PRP, Band3 protein, and Nrf2 gene expression. This regulation reduces lipid peroxidation, minimizes LPO and MDA production, and preserves cell integrity, ultimately decreasing the hemolysis rate under oxidative stress.